Blenderella character modeling in Blender 2.5 (Blender Open Movie Workshop DVD Series, 2011)
In this DVD, Angela Guenette walks you through her approach on modeling a character within Blender 2.5. She demonstrates the tools used in Blender and techniques on how to create efficient topology with clean edge flow. This will facilitate the creation of facial and body deformation for rigging and animation use.